PENGEMBANGAN INDUSTRI RUMAH TANGGA BERBASIS AIR KELAPA TUA DAN IKAN LELE DI DESA ANDOOLO UTAMA - Muhaimin Hamzah; Indriyani Nur; La Ode Santiaji Bande; Weka Gusmiarty Abdullah; Putu Arimbawa; Rizal Adi Saputra; Mundeh, Marianne; Dwina Angelina Sipayung; Nabila Saskia Arham (Universitas Mataram, 2024)
This study aims to enhance the welfare of the Andoolo Utama Village community by developing a home industry based on mature coconut water and catfish. The objective is to utilize local resources to create value-added products, namely Nata de Coco and Catfish Floss. The methods employed include field identification, design discussions, socialization, and product-making training. The results indicate that the training successfully improved the knowledge and skills of the community in processing raw materials, while also encouraging active participation in developing home industries. It is expected that this initiative will open new business opportunities and increase the income of the village community.